Synthesis and Fluorescence Properties of Europium, Terbium Doped Zn^2＋, Cd^2＋, and Cr^3＋ Complexes - 温孝春 赵永亮 王连蒙 张梅 高德青 (Journal of rare earths, 2007)
Europium and terbium complexes with strong fluorescence intensity and long fluorescence lifetime were prepared. By replacing half of the europium or terbium ion with M （M = Zn^2＋, Cd^2＋, and Cr^3＋） using the doped method, and then incorporating it with 18-crown-6 ether and terephthalic acid, six heteronuclear samples EuZnLL＇Cl3·3H2O（1）, EuCdLL2＇Cl3·5H2O（2）, EuCrLL＇Cl4· 4H2O（3）, TbZnLL＇Cl3·4H2O（4）, TbCdLL＇2Cl3·4H2O（5）, and TbCrLL＇2Cl4 ·4H2O（6） （L = terephthalic acid, L＇= 18-Crown-6 ether） were obtained. The elemental analysis, molar conductivities, rare earth complexometry, Fourier Transform Infrared Spectroscopy （FT-IR）, ultraviolet （UV）, TGA, fluorescence intensity, and fluorescence lifetime of the samples were measured. The results showed that there were good luminescence properties for heteronuclear complexes （1）, （2）, （4）, and （5）, which were even stronger than those of the homonuclear complexes Eu2LL＇2Cl4·4H2O and Tb2LL＇2Cl4 ·4H2O, but the luminescence properties of EuCrLL＇Cl4·4H2O, TbCrLL＇Cl4·4H2O were very weak. A possible luminescence mechanism was suggested by the organic-inorganic doped mechanism and the law of intramolecular energy transfer.